RNA profiling identifies novel, photoperiodhistory dependent markers associated with enhanced saltwater performance in juvenile Atlantic salmon - Iversen, Marianne; Mulugeta, Teshome Dagne; Blikeng, Børge Gellein; West, Alexander Christopher; Jørgensen, Even Hjalmar; Sandve, Simen Rød; Hazlerigg, David (PLOS ONE, 2020)
Atlantic salmon migrate to sea following completion of a developmental process known as smolting, which establishes a seawater (SW) tolerant phenotype. Smolting is stimulated by exposure to long photoperiod or continuous light (LL) following a period of exposure to short photoperiod (SP), and this leads to major changes in gill ion exchange and osmoregulatory function. Here, we performed an RNAseq experiment to discover novel genes involved in photoperiod-dependent remodeling of the gill. This revealed a novel cohort of genes whose expression rises dramatically in fish transferred to LL following SP exposure, but not in control fish maintained continuously on LL or on SP. A follow-up experiment revealed that the SP-history dependence of LL induction of gene expression varies considerably between genes. Some genes were inducible by LL exposure after only 2 weeks exposure to SP, while others required 8 weeks prior SP exposure for maximum responsiveness to LL. Since subsequent SW growth performance is also markedly improved following 8 weeks SP exposure, these photoperiodic history-dependent genes may be useful predictive markers for full smolt development.